(untitled) (Ahkam: Jurnal Hukum Islam, 2024)
East Pademawu people, which is in majority Madurese owns a belief that non-identical twins (male and female) have been born then the twin’s raising must be sperately done. They believe that there will be an illness or even death in the future experiencef by the either one of twins. In this research there are two formulated problem 1) What is the practice of separate raising of twins after 40 days in East Pademawu Village, Pademawu District, Pamekasan Regency? 2) What is the practice of seperate-twin raising after 40 days from the urf perspective in East Pademawu Village, Pademawu District, Pamekasan Regency? From the research findings, it can be concluded that the practice of separate raising of twins in East Pademawu Village, Pademawu District, Pamekasan Regency does not violate Islamic law and it is permissible to carry out this tradition among the community provided that society does not consider such a yradition as a belief that may lead to shirk. Separate raising of twins is included in ’urf shahih as long as it does not violate the existing rules, Islamic law, and regulations.